Strategies for Determining German Nouns’ Gender by College Students - Kiyko, Svitlana; Kiyko, Yuriy; Drebet, Viktor (East European Journal of Psycholinguistics, 2020)
The article is dedicated to the study of strategies for determining the gender of nouns of the German language by Ukrainian-speaking first-year-students at the Yuriy Fedkovych National University of Chernivtsi, Ukraine. The purpose of the study is to establish the strategies for determining the gender of nouns on the basis of phonetic, morphological, and semantic criteria and experimentally trace the impact of interlingual and intralingual interference in the process of gender categorization of nouns. The material of the study included 60 nouns, out of which 30 were phonetic equivalents and 30 – semantic ones. Each group contained 10 nouns of the masculine, feminine, and neuter gender, respectively, with the same number of structurally different nouns among them, which were selected according to semantic, morphological, and phonetic rules of gender identification. To identify strategies for determining the gender of German nouns, two psycholinguistic experiments were held with a month interval. The experiments involved 30 first-year-students at the University of Chernivtsi (German department), who had to decide whether the noun gender specified in DMDX program is correct. Thus, the article in half of the given nouns was set incorrectly in the program. The obtained results indicate that the gender of the noun of the native language significantly affects gender determining of the German phonetic equivalent (85% of all mistakes in determining the gender in Experiment 1 and 47% – in Experiment 2). The students also focus on the suffixes or endings of German nouns when choosing the correct gender. Phonetic or semantic rules for determining gender play a secondary role. The gender of a noun in the native language prevents the correct choice of the gender in the German language, which is twice as often recorded for phonetic equivalents.